ANALISIS ECOLOGICAL CITIZENSHIP MASYARAKAT PEMATANG SULUR DALAM PENGELOLAAN SAMPAH MELALUI PROGRAM BANK SAMPAH DI TPS 3R SULUR BERKAH - Sekar Ayu; Melisa; Hendra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low level of public awareness and participation in waste management in Pematang Sulur Village, Telanaipura District, Jambi City. This study aims to determine community participation in ecological citizenship through the waste bank program and the supporting and inhibiting factors in realizing it.This study employed a qualitative and descriptive approach, with data collection techniques including observation, interviews, and documentation. The research informants included the head of the waste bank at the Sulur Berkah 3R Waste Management Site (TPS 3R), the Environmental Agency, and the Pematang Sulur community, selected using purposive sampling. Data analysis was conducted through data collection, reduction, presentation, and drawing conclusions using triangulation of sources, techniques, and time.The results indicate that community ecological citizenship in waste management through the waste bank program at the Sulur Berkah 3R Waste Management Site (TPS 3R) is suboptimal due to low public participation and awareness in sorting and managing waste. Nevertheless, the waste bank program has had positive impacts in the form of increased environmental awareness and economic benefits. The supporting factors include the existence of a waste bank program, support from 3R TPS managers, and some public awareness, while the inhibiting factors include the lack of understanding of waste management in the community and minimal public participation.